A novel application for Aquacel Ag in paediatric frostbite. Issue 1 (January 2019) - Ghumman, Ammara; Malic, Claudia
Abstract: Frostbite is well documented in the military and in countries with extreme temperatures and seen more commonly in adults (age 30–49 y). It is most likely due to increased exposure to cold or risk-taking behavior. Severity of injury depends on a number of factors including absolute temperature, wind chill, duration of exposure, wet/dry cold, immersion, clothing quality and substance abuse. Anatomically, the hands and feet account for 90% of reported injuries. The acute management of the frostbite wounds varies according to the depth of the injuries. Flammazine is frequently used for management of the frostbite wounds. Aquacel Ag has been used extensively for management of superficial and mixed partial thickness burns. To present, Aquacel Ag has not been documented in the literature as alternative dressings for frostbite wounds. This is a case series of three paediatric patients (two male, one female) where Aquacel Ag has been used for their second and third degree frostbite wounds. All wounds completely epithelialized within 19 days from the time of the injury with no clinical signs of infection. Aquacel Ag should be considered in the armamentarium of dressings used on frostbite wounds.